Statutes of Ohio and of the Northwestern Territory 230, ch. 98, § 10 (Vol. 1. Cincinnati, 1833) - (:unkn) unknown (General Publisher, 1833)
And if any person within this territory, shall challenge, by word or in writing, the person of another to fight at sword, rapier, pistol, or other deadly weapon, the person so challenging, shall forfeit and pay for every such offense, being thereof lawfully convicted, in any court of record within the county wherein the offense shall be committed, having competent jurisdiction by the testimony of one or more witnesses, or by the confession of the party offending, a sum not exceeding two hundred and fifty dollars, not less than fifty dollars
--
Keywords: DUELING